A Metacognitive Approach in Teaching Ulumul Qur’an and Ulumul Hadith: A Study of Students at Stain Mandailing Natal - Nelmi Hayati; Nur Hamidah Pulungan; Aulya Adhli; Edriagus Saputra; Arwansyah bin Kirin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study examines the implementation of a metacognitive approach in teaching Ulumul Qur’an and Ulumul Hadith at STAIN Mandailing Natal. Using a descriptive qualitative approach, data were collected through classroom observations, semi-structured interviews, and documentation involving lecturers and students. The findings indicate that metacognitive strategies such as reflective questioning, analytical discussion, learning journals, and self-assessment contributed to improving students’ conceptual understanding, analytical thinking, and reflective awareness in studying Qur’anic and hadith sciences. Students demonstrated stronger engagement in contextual interpretation, sanad analysis, and matn evaluation across the planning, monitoring, and evaluation stages. This study contributes to the development of a contextual metacognitive learning model for Islamic higher education.